Sensing Mechanisms: Calcium Signaling Mediated Abiotic Stress in Plants - Xu, Tongfei; Niu, Junfeng; Jiang, Zhonghao (Frontiers in Plant Science, 2022)
Plants are exposed to various environmental stresses. The sensing of environmental cues and the transduction of stress signals into intracellular signalling are initial events in the cellular signalling network. As a second messenger, Ca2+ links environmental stimuli to different biological processes, such as growth, physiology and sensing of and response to stress. An increase in intracellular calcium concentrations ([Ca2+]i) is a common event in most stress-induced signal transduction pathways. In recent years, significant progress has been made in research related to the early events of stress signalling in plants, particularly in the identification of primary stress sensors. This review highlights current advances that are beginning to elucidate the mechanisms by which abiotic environmental cues are sensed via Ca2+ signals. Additionally, this review discusses important questions about the integration of the sensing of multiple stress conditions and subsequent signalling responses that need to be addressed in the future.